5.26.4 Problems 301 to 400

Table 5.1125: Second order, Linear, Homogeneous and non-constant coefficients

#

ODE

Mathematica

Maple

8291

\[ {}x y^{\prime \prime }+y^{\prime }+x y = 0 \]

8292

\[ {}y^{\prime }+x y^{\prime \prime }+\left (x -\frac {4}{x}\right ) y = 0 \]

8293

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (9 x^{2}-4\right ) y = 0 \]

8294

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (36 x^{2}-\frac {1}{4}\right ) y = 0 \]

8295

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (25 x^{2}-\frac {4}{9}\right ) y = 0 \]

8296

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (2 x^{2}-64\right ) y = 0 \]

8297

\[ {}x y^{\prime \prime }+2 y^{\prime }+4 y = 0 \]

8298

\[ {}x y^{\prime \prime }+3 y^{\prime }+x y = 0 \]

8299

\[ {}x y^{\prime \prime }-y^{\prime }+x y = 0 \]

8300

\[ {}x y^{\prime \prime }-5 y^{\prime }+x y = 0 \]

8301

\[ {}x^{2} y^{\prime \prime }+\left (x^{2}-2\right ) y = 0 \]

8302

\[ {}4 x^{2} y^{\prime \prime }+\left (16 x^{2}+1\right ) y = 0 \]

8303

\[ {}x y^{\prime \prime }+3 y^{\prime }+x^{3} y = 0 \]

8304

\[ {}9 x^{2} y^{\prime \prime }+9 x y^{\prime }+\left (x^{6}-36\right ) y = 0 \]

8305

\[ {}y^{\prime \prime }-x^{2} y = 0 \]

8306

\[ {}x y^{\prime \prime }+y^{\prime }-7 x^{3} y = 0 \]

8308

\[ {}x^{2} y^{\prime \prime }+4 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

8309

\[ {}16 x^{2} y^{\prime \prime }+32 x y^{\prime }+\left (x^{4}-12\right ) y = 0 \]

8310

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (16 x^{2}+3\right ) y = 0 \]

8502

\[ {}y^{\prime \prime } \cos \left (x \right ) = y^{\prime } \]

8606

\[ {}2 x^{2} y^{\prime \prime }+x y^{\prime }-y = 0 \]

8607

\[ {}2 x^{2} y^{\prime \prime }-3 x y^{\prime }+2 y = 0 \]

8608

\[ {}9 x^{2} y^{\prime \prime }+2 y = 0 \]

8609

\[ {}2 x^{2} y^{\prime \prime }+5 x y^{\prime }-2 y = 0 \]

8610

\[ {}x^{2} y^{\prime \prime }+2 x y^{\prime }-12 y = 0 \]

8611

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }-9 y = 0 \]

8612

\[ {}x^{2} y^{\prime \prime }-3 x y^{\prime }+4 y = 0 \]

8613

\[ {}x^{2} y^{\prime \prime }-5 x y^{\prime }+9 y = 0 \]

8614

\[ {}x^{2} y^{\prime \prime }+5 x y^{\prime }+5 y = 0 \]

8626

\[ {}x y^{\prime \prime }+y^{\prime }-x y = 0 \]

8657

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-1\right ) y = 0 \]

8760

\[ {}\left (t^{2}+9\right ) y^{\prime \prime }+2 t y^{\prime } = 0 \]

8761

\[ {}t^{2} y^{\prime \prime }-3 t y^{\prime }+5 y = 0 \]

8762

\[ {}t y^{\prime \prime }+y^{\prime } = 0 \]

8763

\[ {}t^{2} y^{\prime \prime }-2 y^{\prime } = 0 \]

8764

\[ {}y^{\prime \prime }+\frac {\left (t^{2}-1\right ) y^{\prime }}{t}+\frac {t^{2} y}{\left (1+{\mathrm e}^{\frac {t^{2}}{2}}\right )^{2}} = 0 \]

8765

\[ {}t y^{\prime \prime }-y^{\prime }+4 t^{3} y = 0 \]

8954

\[ {}\frac {x y^{\prime \prime }}{1-x}+x y = 0 \]

8956

\[ {}\frac {x y^{\prime \prime }}{-x^{2}+1}+y = 0 \]

8957

\[ {}y^{\prime \prime } = \left (x^{2}+3\right ) y \]

8961

\[ {}y^{\prime \prime } \sin \left (2 x \right )^{2}+y^{\prime } \sin \left (4 x \right )-4 y = 0 \]

8963

\[ {}y^{\prime \prime }+2 x y^{\prime }+\left (x^{2}+1\right ) y = 0 \]

8964

\[ {}y^{\prime \prime }+2 \cot \left (x \right ) y^{\prime }-y = 0 \]

8965

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

8981

\[ {}x y^{\prime \prime }-\left (2 x +1\right ) y^{\prime }+\left (1+x \right ) y = 0 \]

9139

\[ {}y^{\prime \prime }+\frac {2 y^{\prime }}{x}+\frac {a^{2} y}{x^{4}} = 0 \]

9140

\[ {}\left (-x^{2}+1\right ) y^{\prime \prime }-x y^{\prime }-c^{2} y = 0 \]

9143

\[ {}y^{\prime \prime }+\cot \left (x \right ) y^{\prime }+4 \csc \left (x \right )^{2} y = 0 \]

9145

\[ {}y^{\prime \prime }+\tan \left (x \right ) y^{\prime }+\cos \left (x \right )^{2} y = 0 \]

9151

\[ {}y^{\prime \prime }-\frac {y^{\prime }}{\sqrt {x}}+\frac {y \left (-8+\sqrt {x}+x \right )}{4 x^{2}} = 0 \]

9152

\[ {}\cos \left (x \right )^{2} y^{\prime \prime }-2 \cos \left (x \right ) \sin \left (x \right ) y^{\prime }+\cos \left (x \right )^{2} y = 0 \]

9157

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+2 \left (x^{2}+1\right ) y = 0 \]

9158

\[ {}4 x^{2} y^{\prime \prime }+4 x^{5} y^{\prime }+\left (x^{8}+6 x^{4}+4\right ) y = 0 \]

9160

\[ {}x y^{\prime \prime }+2 y^{\prime }-x y = 0 \]

9161

\[ {}x y^{\prime \prime }+2 y^{\prime }+x y = 0 \]

9168

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-5\right ) y = 0 \]

9169

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

9173

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }-2 x y^{\prime }+2 y = 0 \]

9174

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }-6 x y^{\prime }+12 y = 0 \]

9175

\[ {}\left (x^{2}+3\right ) y^{\prime \prime }-7 x y^{\prime }+16 y = 0 \]

9176

\[ {}\left (x^{2}-1\right ) y^{\prime \prime }+8 x y^{\prime }+12 y = 0 \]

9177

\[ {}3 y^{\prime \prime }+x y^{\prime }-4 y = 0 \]

9178

\[ {}5 y^{\prime \prime }-2 x y^{\prime }+10 y = 0 \]

9179

\[ {}y^{\prime \prime }-x^{2} y^{\prime }-3 x y = 0 \]

9180

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }+2 x y^{\prime }-2 y = 0 \]

9181

\[ {}y^{\prime \prime }+x y^{\prime }-2 y = 0 \]

9182

\[ {}\left (x^{2}-6 x +10\right ) y^{\prime \prime }-4 \left (x -3\right ) y^{\prime }+6 y = 0 \]

9183

\[ {}\left (x^{2}+6 x \right ) y^{\prime \prime }+\left (3 x +9\right ) y^{\prime }-3 y = 0 \]

9184

\[ {}t y^{\prime \prime }+\left (t^{2}-1\right ) y^{\prime }+t^{2} y = 0 \]

9185

\[ {}t^{2} y^{\prime \prime }-t \left (2+t \right ) y^{\prime }+\left (2+t \right ) y = 0 \]

9186

\[ {}t y^{\prime \prime }-\left (t +1\right ) y^{\prime }+y = 0 \]

9187

\[ {}\left (1-t \right ) y^{\prime \prime }+t y^{\prime }-y = 0 \]

9188

\[ {}x^{2} y^{\prime \prime }+x y^{\prime }+\left (x^{2}-\frac {1}{4}\right ) y = 0 \]

9189

\[ {}t y^{\prime \prime }-\left (t +1\right ) y^{\prime }+y = 0 \]

9190

\[ {}\left (1-t \right ) y^{\prime \prime }+t y^{\prime }-y = 0 \]

9191

\[ {}y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

9192

\[ {}\left (x^{2}+1\right ) y^{\prime \prime }-4 x y^{\prime }+6 y = 0 \]

9193

\[ {}\left (1-x \right ) y^{\prime \prime }+x y^{\prime }-y = 0 \]

9194

\[ {}2 y^{\prime \prime }+x y^{\prime }+3 y = 0 \]

9195

\[ {}y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

9196

\[ {}\left (1-x \right ) y^{\prime \prime }+x y^{\prime }-y = 0 \]

9197

\[ {}y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

9198

\[ {}\left (-x^{2}+4\right ) y^{\prime \prime }+x y^{\prime }+2 y = 0 \]

9199

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (-16 x^{2}+3\right ) y = 0 \]

9200

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

9201

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

9202

\[ {}\left (x^{2}-2 x \right ) y^{\prime \prime }+\left (-x^{2}+2\right ) y^{\prime }+\left (2 x -2\right ) y = 0 \]

9203

\[ {}4 x^{2} y^{\prime \prime }+\left (-8 x^{2}+4 x \right ) y^{\prime }+\left (4 x^{2}-4 x -1\right ) y = 0 \]

9204

\[ {}y^{\prime \prime }+4 x y^{\prime }+\left (4 x^{2}+2\right ) y = 0 \]

9205

\[ {}\left (2 x +1\right ) y^{\prime \prime }-2 y^{\prime }-\left (2 x +3\right ) y = 0 \]

9206

\[ {}x y^{\prime \prime }-\left (2+2 x \right ) y^{\prime }+\left (x +2\right ) y = 0 \]

9207

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }+\left (x^{2}+2\right ) y = 0 \]

9208

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (-16 x^{2}+3\right ) y = 0 \]

9209

\[ {}4 x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (4 x^{2}+3\right ) y = 0 \]

9210

\[ {}x^{2} y^{\prime \prime }-2 x y^{\prime }-\left (x^{2}-2\right ) y = 0 \]

9211

\[ {}x^{2} y^{\prime \prime }-2 x \left (1+x \right ) y^{\prime }+\left (x^{2}+2 x +2\right ) y = 0 \]

9212

\[ {}x^{2} y^{\prime \prime }-2 x \left (x +2\right ) y^{\prime }+\left (x^{2}+4 x +6\right ) y = 0 \]

9213

\[ {}x^{2} y^{\prime \prime }-4 x y^{\prime }+\left (x^{2}+6\right ) y = 0 \]

9214

\[ {}\left (x -1\right ) y^{\prime \prime }-x y^{\prime }+y = 0 \]

9215

\[ {}4 x^{2} y^{\prime \prime }-4 x \left (1+x \right ) y^{\prime }+\left (2 x +3\right ) y = 0 \]